The Canadian Natural Health Products (NHP) regulations: industry perceptions and compliance factors - Boon Heather; Laeeque Hina; Kachan Natasha; Cohen Jillian; D'Cruz Joseph (BMC Health Services Research, 2006)
Abstract Background The use of natural health products, such as vitamins, minerals, and herbs, by Canadians has been increasing with time. As a result of consumer concern about the quality of these products, the Canadian Department of Health created the Natural Health Products (NHP) Regulations. The new Canadian regulations raise questions about whether and how the NHP industry will be able to comply and what impact they will have on market structure. The objectives of this study were to explore who in the interview sample is complying with Canada's new NHP Regulations (i.e., submitted product licensing applications on time); and explore the factors that affect regulatory compliance. Methods Twenty key informant interviews were conducted with employees of the NHP industry. The structured interviews focused on the level of satisfaction with the Regulations and perceptions of compliance and non-compliance. Interviews were tape recorded and then transcribed verbatim. Data were independently coded, using qualitative content analysis. Team meetings were held after every three to four interviews to discuss emerging themes. Results The major finding of this study is that most (17 out of 20) companies interviewed were beginning to comply with the new regulatory regime. The factors that contribute to likelihood of regulatory compliance were: perceptions and knowledge of the regulations and business size. Conclusion The Canadian case can be instructive for other countries seeking to implement regulatory standards for natural health products. An unintended consequence of the Canadian NHP regulations may be the exit of smaller firms, leading to industry consolidation.